2006
DOI: 10.1073/pnas.0604283103
|View full text |Cite|
|
Sign up to set email alerts
|

A deletion defining a common Asian lineage ofMycobacterium tuberculosisassociates with immune subversion

Abstract: Six major lineages of Mycobacterium tuberculosis appear preferentially transmitted amongst distinct ethnic groups. We identified a deletion affecting Rv1519 in CH, a strain isolated from a large outbreak in Leicester U.K., that coincidentally defines the East African-Indian lineage matching a major ethnic group in this city. In broth media, CH grew less rapidly and was less acidic and H 2 O 2 -tolerant than referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 25 publications
(28 reference statements)
4
86
0
Order By: Relevance
“…Importantly, LSPs in certain M. tuberculosis strains have been linked to host immune modification. In particular, Central Asian (CAS) strains possess an LSP that has been associated with an increased capacity to promote host IL-10 production as an immune evasion strategy (39). Although RD Rio strains have lost a phenoglycolipid involved in inhibiting proinflammatory cytokines due to a deletion within the pks15/1 gene, we speculate that RD Rio M. tuberculosis may dampen immune recognition through the deletion of two of its surface antigens (PPE55 and PPE56), among other potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, LSPs in certain M. tuberculosis strains have been linked to host immune modification. In particular, Central Asian (CAS) strains possess an LSP that has been associated with an increased capacity to promote host IL-10 production as an immune evasion strategy (39). Although RD Rio strains have lost a phenoglycolipid involved in inhibiting proinflammatory cytokines due to a deletion within the pks15/1 gene, we speculate that RD Rio M. tuberculosis may dampen immune recognition through the deletion of two of its surface antigens (PPE55 and PPE56), among other potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that strains with the RD750 deletion are a prominent cause of tuberculosis among Asians in the United Kingdom and in the Indian subcontinent. The RD750 deletion appears to have increased, rather than decreased, the capacity of this lineage of MTB to cause immune deviation and contribute to its persistence and outbreak potential in human populations [13]. It has been suggested that deletions in the RD149 and RD152 regions may be due to transposition and homologous recombination events between adjacent IS6110 fragments.…”
Section: Spoligotypesmentioning
confidence: 99%
“…These deletions affect the Rv1519 and Rv1520 genes which have been shown to up-regulate the anti-inflammatory cytokine IL-10 in the human monocyte derived macrophages; thus the deletions appear to favor the intracellular survival of the pathogen [13].…”
Section: Introductionmentioning
confidence: 99%
“…All cells were cultured in triplicate in 100 ml RPMI enriched with 10% heat-inactivated fetal calf serum (GIBCO, Mowbray, South Africa) and 100 U/ml penicillin G (Merck, Modderfontein, South Africa) in 96-well plates. The M. tuberculosis strain H37Rv was prepared as previously described (30) and cells were infected at a multiplicity of infection of 1:1. A new vial was thawed for every experiment.…”
Section: Infection Assay Of Monocytes and Alveolar Macrophages With Mmentioning
confidence: 99%